2002
DOI: 10.1152/jn.2002.88.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volitional Inhibition on Cortical Inhibitory Mechanisms

Abstract: To investigate the effect of volitional inhibition on cortical inhibitory mechanisms, we performed transcranial magnetic stimulation (TMS) studies with a Go/NoGo reaction task in seven healthy subjects. Subjects were asked to extend their right index finger only after Go, but to remain relaxed after NoGo. Single- and paired-pulse TMS were triggered at the average reaction time for the Go response in each subject after Go or NoGo cues. Motor evoked potentials were recorded in the extensor indicis proprius (EIP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
112
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 26 publications
14
112
3
Order By: Relevance
“…In contrast, the StopInhibit trials show a peak activation that is delayed by 2 s, as if the inhibition emerged in time to prevent activation from reaching a critical (response) threshold at a critical time. This finding provides blood oxygenation level-dependent (BOLD) evidence consistent with transcranial magnetic stimulation (TMS) studies showing that volitional response inhibition increases intracortical (GABAergic) inhibition in the motor cortex region (Sohn et al, 2002).…”
Section: Experiments 1: Whole-brain Analysessupporting
confidence: 80%
“…In contrast, the StopInhibit trials show a peak activation that is delayed by 2 s, as if the inhibition emerged in time to prevent activation from reaching a critical (response) threshold at a critical time. This finding provides blood oxygenation level-dependent (BOLD) evidence consistent with transcranial magnetic stimulation (TMS) studies showing that volitional response inhibition increases intracortical (GABAergic) inhibition in the motor cortex region (Sohn et al, 2002).…”
Section: Experiments 1: Whole-brain Analysessupporting
confidence: 80%
“…Given that the instruction to our subjects was to avoid contracting the left resting arm (see Materials and Methods), it would be theoretically possible that the reduction in SICI might be related to "volitional inhibition" (i.e., to the intent to suppress unwanted voluntary movements in the resting arm) (Waldvogel et al, 2000). However, such interpretation seems unlikely because volitional inhibition results in increases in SICI and suppression of corticospinal excitability, opposite to our results (Waldvogel et al, 2000;Sohn et al, 2002;Coxon et al, 2006).…”
Section: Sicicontrasting
confidence: 60%
“…However, similar to SICI, LICI decreases with voluntary contraction of the target muscle [18] . Another study examined the effect of volitional inhibition and found that LICI was decreased during motor task performance [19] illustrating that this circuit can be modulated by voluntary activity. Furthermore, vibrotactile stimulation of a muscle suppresses LICI within that muscle and increases it in surrounding muscles [20] .…”
Section: Role Of Intracortical Inhibition In Human Motor Behaviormentioning
confidence: 99%
“…These data suggest that LICI may also impact movement selection and modify motor behavior. Thus, despite the paucity of literature, it appears that the LICI circuit also plays a role in regulating motor output to the muscles during motor tasks [19] .…”
Section: Role Of Intracortical Inhibition In Human Motor Behaviormentioning
confidence: 99%